Do Visual and Vestibular Inputs Compensate for Somatosensory Loss in the Perception of Spatial Orientation? Insights from a Deafferented Patient - Bringoux, Lionel; Scotto Di Cesare, Cécile; Borel, Liliane; Macaluso, Thomas; Sarlegna, Fabrice R. (Frontiers in Human Neuroscience, 2016)
The present study aimed at investigating the consequences of a massive loss of somatosensory inputs on the perception of spatial orientation. The occurrence of possible compensatory processes for external (i.e., object) orientation perception and self-orientation perception was examined by manipulating visual and/or vestibular cues. To that aim, we compared perceptual responses of a deafferented patient (GL) with respect to age-matched Controls in two tasks involving gravity-related judgments. In the first task, subjects had to align a visual rod with the gravitational vertical (i.e., Subjective Visual Vertical: SVV) when facing a tilted visual frame in a classic Rod-and-Frame Test. In the second task, subjects had to report whether they felt tilted when facing different visuo-postural conditions which consisted in very slow pitch tilts of the body and/or visual surroundings away from vertical. Results showed that, much more than Controls, the deafferented patient was fully dependent on spatial cues issued from the visual frame when judging the SVV. On the other hand, the deafferented patient did not rely at all on visual cues for self-tilt detection. Moreover, the patient never reported any sensation of tilt up to 18 deg contrary to Controls, hence showing that she did not rely on vestibular (i.e., otoliths) signals for the detection of very slow body tilts either. Overall, this study demonstrates that a massive somatosensory deficit substantially impairs the perception of spatial orientation, and that the use of the remaining sensory inputs available to a deafferented patient differs regarding whether the judgment concerns external versus self-orientation.